Effectiveness of a structured teaching programme on knowledge of breast cancer and skill of breast self-examination: a quasi-experimental study in rural women - Molly, John; Mercy, P. J. (International Journal Of Community Medicine And Public Health, 2016)
Background: The women in rural area lacked knowledge regarding breast cancer and breast self-examination (BSE). The study was designed to investigate the effectiveness of structured teaching programme to enhance knowledge and asses the skill of BSE among mahila mandal women. Methods: Quasi experimental one group pre-test and post-test design with the aid of a questionnaire and interview schedule was conducted among 42 mahila mandal women from three villages under Mugalur Community health and training centre, Karnataka. The pre-test knowledge was assessed using structured interview schedule and BSE skill was assessed by an observation check list. Results: Out of 42 women, most of the participants gained knowledge about breast cancer and developed skill in doing BSE. The mean pre-test knowledge score (7.6±3.0) was less than the post-test knowledge score (24.9±2.7). The mean pre-test skill score (0.7±1.0) was also less than the post-test skill score (12.4±2.0). The paired t value between the pre-test and post-test knowledge and skill score was statistically significant at 0.001 level. No significant association was existed between the selected baseline variables age, education, income, marital status and years of experience in mahila mandal with pre-test knowledge and skill score of breast cancer and BSE. Conclusions: The study concluded that structured teaching programme was an effective strategy in improving the knowledge and skill of women regarding breast cancer and BSE.